Segregation of coal particles during charging into coking tower - Koval, Valentyn; Miroshnichenko, Denis Viktorovich; Avdeyuk, Illia; Miroshnychenko, Mykhailo; Nedbailo, Serhii (Національний технічний університет "Харківський політехнічний інститут", 2025)
This study investigated coal segregation at a coking plant, focusing on particle size and quality. Conducted at PJSC "ACP," it revealed uneven ash content distribution, with the 25–50 mmfraction showing high variability (6.8–32.1%) and the 1–6 mm fraction the lowest (~7.3%). Key findings include: Ash content varied across size classes, with the 25–50 mm fraction having 13.1% on average. Stable technological properties and granulometric composition during loading. Significant quality deviations in the extreme rows of the coal tower. Need for measures to minimize segregation and stabilize coke quality.
Keywords: coal segregation; aoking plant; particle size; coal qualitya; sh content; coal tower; granulometric composition; segregation control; blast furnace coke; coal preparation